RELATIONSHIP BETWEEN MARKET PENETRATION STRATEGY AND CUSTOMER EXPERIENCE MANAGEMENT IN MOBILE SERVICE PROVIDERS IN KENYA - Gecheo,, P. Ooga; Thuo, J. Kuria; Byaruhanga, J. (IJRDO - Journal of Business Management, 2016)
One of the most important questions faced by business leaders in the strategic management processis a choice of how to adopt a market penetration strategy whereby a firm gains more usage fromexisting customers and also seeks to attract customers from existing competitors. The mobileservice industry has recently experienced a quick succession of mobile service innovations, indeciding on the optimal timing of each service launch, carriers need to consider a complex arrayof technological, regulatory, and strategic factors. In spite of wide-ranging research on marketpenetration strategy, very little empirical research has observed the relationship between themarket penetration strategies and competitiveness in mobile telecommunication sector. Based onthis background, this study sought to investigate market penetration strategy and customerexperience management of mobile telecommunication service providers in Kenya. The studypopulation consisted of all the mobile Service providers in Kenya which according to a listobtained from Communications Commission of Kenya as at July 2010 are four. Given the smallnumber of firms a census study was conducted. The findings of the study revealed that there weremean differences in market penetration strategy implementation and customer experiencemanagement between these four mobile service providers. This study was significant since it ishoped that findings and recommendation of the study will provides a greater understanding ofappropriate market penetration strategy implementation framework as well as how marketpenetration strategies influences customer experience management. In this sense, the study willcontributes to knowledge in terms of effective strategy implementation and its contribution toorganizational performance.